Volume 1: Turbomachinery 1998
DOI: 10.1115/98-gt-091
|View full text |Cite
|
Sign up to set email alerts
|

Physical Explanations of Tip Leakage Flow Field in an Axial Compressor Rotor

Abstract: Structure of a tip leakage flow field in an axial compressor rotor has been investigated by detailed numerical simulations and appropriate post-processing. Physical explanations of the structure are made in terms of vortex-core identification, normalized helicity, vortex-lines, limiting streamlines, etc. The onset of the discrete tip leakage vortex is located on the suction surface at some distance from the leading edge. The vortex core with high vorticity is generated from a shear layer between the leakage je… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 25 publications
(37 reference statements)
0
8
0
Order By: Relevance
“…Kang and Hirsch [6j experimentally observed that the flow in the linear cascade tip had a multiple vortex structure, consisting of the tip leakage vortex, the tip separation vortex and the secondary vortex. Inoue et al [7][8][9] studied the influence of the tip clearance size on the tip leakage vortex in an isolated rotor. Foley and Ivey [~°] observed that the leakage jet from both stators and rotors rolled up into a vortex downstream of Received June 2, 2005 Hongwu ZHANG: Associate Professor their respective blade rows in the third stage of a low-speed four-stage axial compressor.…”
Section: Introduction Backgroundmentioning
confidence: 99%
“…Kang and Hirsch [6j experimentally observed that the flow in the linear cascade tip had a multiple vortex structure, consisting of the tip leakage vortex, the tip separation vortex and the secondary vortex. Inoue et al [7][8][9] studied the influence of the tip clearance size on the tip leakage vortex in an isolated rotor. Foley and Ivey [~°] observed that the leakage jet from both stators and rotors rolled up into a vortex downstream of Received June 2, 2005 Hongwu ZHANG: Associate Professor their respective blade rows in the third stage of a low-speed four-stage axial compressor.…”
Section: Introduction Backgroundmentioning
confidence: 99%
“…However, considering the structural strength and the cost of air entrainment, short slot suction scheme and smaller suction flow are the goals we want to pursue. According to the research viewpoints of Storer and Inoue et al (Storer et al 1990;Inoue et al 1989Inoue et al , 1998, the trajectory of leakage vortex near the stator blade tip coincided with the line of the inclined channel connecting the local minimum static pressure on hub endwall. In addition, the minimum static pressure point on the hub endwall was considered as the onset position of leakage vortex.…”
Section: Effect Of the Endwall Suction On The Compressor Performance mentioning
confidence: 95%
“…This method has been successfully used recently to Figure 10. Trajectories of the leakage vortex cores identified using a semi-analytical method 10 study the tip leakage vortices (Inoue et al, 1998;Furukawa et aL, 1998). bout et aL (1998) have been able to identify the trajectory of a vortex core visually using this method to explain the onset of the tip-leakage vortex.…”
Section: Vortex Core Trajectoriesmentioning
confidence: 99%
“…bout et aL (1998) have been able to identify the trajectory of a vortex core visually using this method to explain the onset of the tip-leakage vortex. Furukawa et al (1998) have explained the role of the vortex breakdown in rotor performance near the stall condition. This method is similar to a critical-point analysis (e.g., Perry and Chong, 1987) except that it uses a semi-analytical streamline construction, which assumes that the local velocity field can be linearly parametrized in a tetrahedral computational cell.…”
Section: Vortex Core Trajectoriesmentioning
confidence: 99%